2021
DOI: 10.3390/conservation1010001
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Habitat Use and Density of the Green Lizard (Lacerta bilineata) in Contrasted Landscapes in France and Italy

Abstract: Habitat modification is a major factor in the decline of reptile populations. The degree of the decline has been shown to be directly related to the intensity of habitat modification. Farming practices and urbanization are just two of the factors involved indicating that the development of practices that minimize or cancel anthropogenic impacts is urgently needed to prevent further declines. This requires knowledge of population ecology of reptiles in both disturbed and pristine habitats. In this paper, we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Concerning hypothesis 2, the wider habitat niche breadth of the largest bodied species (L. with adults being significantly more generalized (Rugiero et al 2021). This is a further confirmation that it is the body size, and not other ecological characteristics, that is strongly associated with the wider habitat niche breadth of this species.…”
Section: General Considerationssupporting
confidence: 54%
See 2 more Smart Citations
“…Concerning hypothesis 2, the wider habitat niche breadth of the largest bodied species (L. with adults being significantly more generalized (Rugiero et al 2021). This is a further confirmation that it is the body size, and not other ecological characteristics, that is strongly associated with the wider habitat niche breadth of this species.…”
Section: General Considerationssupporting
confidence: 54%
“…Furthermore, habitat niche breadth was nearly identical in 1-2 years-old juvenile L. bilineata population cohorts in comparison to similarly-sized lizards of other species. Intraspecific competition avoidance and cannibalism appear to be the main reasons pushing juveniles to minimize habitat overlap with adults in the large-sized L. bilineata at these study areas (Rugiero et al 2021). The same pattern was also recorded from Anolis lizards, with adult male density having significant effects on juvenile perch height, perch width, and substrate use, thus suggesting that strong age-class competition may contribute to the ontogenetic differences in habitat choice Warner 2017a, 2017b).…”
Section: General Considerationsmentioning
confidence: 55%
See 1 more Smart Citation
“…The individuals recorded after the midsummer gap may represent transients rather than lizards occupying the habitat leading up to hibernation, since most of them were absent during the following year. These changing population dynamics during autumn may involve intraspecific aggression in L. bilineata, with many individuals generally being intolerant of other adults and with juveniles, particularly outside the reproductive season, involving serious injuries and mortalities due to conflicts between adults of both sexes [19,38]. The narrow linear nature of hedgerow systems potentially increases contact between individuals during movement.…”
Section: The Midsummer Gapmentioning
confidence: 99%
“…Arthropods, such as Araneae, Coleoptera, Hymenoptera, and Orthoptera, appear to be their primary prey (Korsós 1984; Maier et al 2020). Due to its large body size, the lizard can occasionally even catch small vertebrates, including other lacertids and conspecifics (Nettmann and Rykena 1984; Leu and Petrovan 2022), which is also typical for other taxonomically related species (Angelici et al 1997; Rugiero et al 2021). Previous dietary studies conducted on related species showed that diet composition changes with body size, age, and season (Angelici et al 1997; Crovetto and Salvidio 2013; Sagonas et al 2018).…”
mentioning
confidence: 99%